2016
DOI: 10.1002/chem.201601832
|View full text |Cite
|
Sign up to set email alerts
|

Constrained Cyclopeptides: Biaryl Formation through Pd‐Catalyzed C−H Activation in Peptides—Structural Control of the Cyclization vs. Cyclodimerization Outcome

Abstract: A series of short tryptophan-phenylalanine peptides containing an iodo substituent on the phenyl ring was subjected to Pd-catalyzed CH activation reactions to give the corresponding aryl-indole coupled products. Two types of adducts were generated: cyclomonomer and cyclodimeric peptides; no evidence of oligo- or polymerization products was detected. Contrary to standard peptide macrocyclizations, the factors controlling the fate of the reaction are the number of amino acids between the aromatic residues and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
43
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 40 publications
0
43
0
3
Order By: Relevance
“…[203] Ther eaction was chemoselective for tryptophan in the presence of other amino acid nucleophiles including Ty r, Arg, His,L ys,S er, Met, and Gln. [204,205] Thes tapling reactions were performed either on resin or in solution, providing access to an umber of structurally diverse stapled peptides. [204,205] Thes tapling reactions were performed either on resin or in solution, providing access to an umber of structurally diverse stapled peptides.…”
Section: Tryptophanmentioning
confidence: 99%
“…[203] Ther eaction was chemoselective for tryptophan in the presence of other amino acid nucleophiles including Ty r, Arg, His,L ys,S er, Met, and Gln. [204,205] Thes tapling reactions were performed either on resin or in solution, providing access to an umber of structurally diverse stapled peptides. [204,205] Thes tapling reactions were performed either on resin or in solution, providing access to an umber of structurally diverse stapled peptides.…”
Section: Tryptophanmentioning
confidence: 99%
“…[203][204][205][206][207][208][209] 2010 berichteten Albericio,L avilla und Ruiz-Rodríguez als Erste über eine Konjugation verschiedener Aryliodide an Tr yptophanreste mittels Palladium-katalysierter C-H-Aktivierung (Abbildung 39 A). [204,205] Die Verbrückungsreaktionen wurden entweder an Harz oder in Lçsung durchgeführt, wodurch eine Reihe strukturell verschiedener,verbrückter Peptide erhalten werden konnte. Die beschriebene C-H-Aktivierungsmethode wurde auch fürd ie Herstellung verbrückter Peptide mit Phe-Trp-oder Ty r-Tr p-Verbindungen herangezogen, wobei 3-Iodphenylalanin oder 2-Iodtyrosin verwendet wurde (Abbildung 39 D).…”
Section: Tryptophanunclassified
“…[201] Aufbauend auf früheren C-H-Aktivierungsstrategien zur Arylierung von Indolen [202] wurden in den letzten Jahren mehrere Palladium-und Ruthenium-katalysierte C-H-Aktivierungen entwickelt, um die C-2-Position von Tr yptophanresten zu modifizieren. [203][204][205][206][207][208][209] 2010 berichteten Albericio,L avilla und Ruiz-Rodríguez als Erste über eine Konjugation verschiedener Aryliodide an Tr yptophanreste mittels Palladium-katalysierter C-H-Aktivierung (Abbildung 39 A). [203] Die Reaktion war chemoselektiv fürT ryptophan in Gegenwart anderer Aminosäurenukleophile,w ie Ty r, Arg, His,L ys,S er,M et und Gln.…”
Section: Tryptophanunclassified
“…[2,3] Despite natural peptides continuing to be of great importance, modification of peptides by introduction of nonproteinogenic amino acids can significantly improve their activities and pharmacokinetics as compared to their natural counterparts. [4] In the past decades, significant progress has been made in late-stage modification of peptides, such as sitespecific C À H functionalization of aromatic residues (tryptophan, histidine, and phenylalanine), [5] reactions of the cysteine -SH group, [6] or decarboxylative coupling of C-terminal acids. [7] In contrast, the functionalizations of C(sp 3 )ÀH in peptide amino acid residues are limited, and the reactions mainly focused on arylation and alkynylation.…”
mentioning
confidence: 99%
“…The desired product 3 aa was obtained in 25 % yield by using DBU (0.20 mmol) as the additive and CH 3 CN (2 mL) as the solvent (entry 1). Screening of light sources showed that violet LED (395-400 nm) was optimal as compared to other lights (entries [2][3][4][5]. Replacing DBU with other bases, such as K 3 PO 4 , Na 2 CO 3 , NaOAc, Cs 2 CO 3 , pyridine, and TMEDA did not improve the yield (entry 6, see the Supporting Information for details).…”
mentioning
confidence: 99%